Historic streetscape characterization: Exploring the evolution of street in the Malay royal town - Ismail W.N.W.; Ja'Afar N.H.; Harun N.Z. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by SCOPUS